The cloze procedure as a measure of verbal creativity - Fortez, Glenda Elape 1946- (s.n.], 1973)
This paper determined the possibilities of the cloze procedure as a measure of creativity in a reading task. The research is designed to analyze the responses of 50 grade five pupils which do not correspond exactly to the deleted words in a cloze procedure but which retain synthetic and semantic acceptability, and to find out the correlation between the degree of divergence of responses and creativity as measured in a standardized Creativity test.